Simultaneous Encapsulation of Mixed‐Halide Perovskite on Synthesis Step Using a Thermally Expandable Lamellar Capsule to Fabricate the Multi‐Conversion Layer. Issue 8 (12th February 2023) - Yoo, Jung Hyeon; Kwon, Seok Bin; Yoo, Ho Chan; Choi, Seung Hee; Song, Young Hyun; Kang, Bong Kyun; Seo, Young Soo; Li, Tianyong; Wang, Yuhua; Yoon, Dae Ho
Abstract: Despite the excellent performance of halide perovskite, low stability, and ion exchange between halides have remained obstacles to practical application. Herein, the polymer capsule encapsulated perovskite through the conventional hot‐injection method is reported to overcome the above issues. The residual heat generated during perovskite synthesis is utilized to expand the layer, and the perovskite particles are grown inside the polyethylene capsule. The products are gathered in a powder state, and the whole emission range can be synthesized. The water stability after 6 h soaked in water shows ≈90% and ≈75% for green and red, respectively. Also, due to the suppressed ion exchange, the single multi‐conversion layer for white light generation can be fabricated. Abstract : Halide perovskite nanocrystals (PeNCs) are designed to grow up inside lamellar‐structured polyethylene (PE) capsules. The whole mixed‐halide composition is successfully synthesized maintaining its own excellent luminescence properties. The crystal growth tendency and optical characteristics analyses prove the performance of the synthesized PE@PeNCs, and the further stability test and pellet fabrication support the prospects for practical application.